2002
DOI: 10.2337/diabetes.51.3.808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment With Sulfonylurea Drugs or Insulin on Ischemia-Induced Myocardial Dysfunction in Type 2 Diabetes

Abstract: In patients with diabetes and coronary artery disease, the potential negative role of sulfonylurea drugs is under intensive investigation. We assessed the effects of treatment with glibenclamide or insulin on the extension of left ventricular myocardial dysfunction induced by acute ischemia. Nineteen consecutive patients with type 2 diabetes and coronary artery disease entered the study. Each patient was randomly assigned to either insulin or glibenclamide therapy. Treatment was crossed over after 12 weeks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 39 publications
1
43
0
4
Order By: Relevance
“…These abnormalities were improved when myocytes were incubated with metformin, but glyburide had no beneficial effect (227). Finally, one experiment recently evaluated the relative functional cardiac effects of glyburide versus insulin (228). In this study of patients with type 2 diabetes, left ventricular function was measured by echocardiography after 12-week treatment periods with each agent, attaining similar metabolic control.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…These abnormalities were improved when myocytes were incubated with metformin, but glyburide had no beneficial effect (227). Finally, one experiment recently evaluated the relative functional cardiac effects of glyburide versus insulin (228). In this study of patients with type 2 diabetes, left ventricular function was measured by echocardiography after 12-week treatment periods with each agent, attaining similar metabolic control.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…Thus, in certain populations with an increased incidence and prevalence of cardiovascular disease, treatments that may unexpectedly interfere with natural PC mechanisms (which would be triggered during transient premonitory episodes of ischemia, such as angina) could increase morbidity and mortality. Sulfonylureas are among the most widely used pharmaceuticals in the treatment of type 2 diabetes mellitus but have been associated with an unexpected and unexplained small increase in cardiovascular mortality in large epidemiology studies (57,58). Certain sulfonylureas are known to inhibit the mitoK ATP , and we have found that glibenclamide (the prototype first-generation sulfonylurea) can abolish the MPT protection of Dz as effectively as 5HD can (S.-H. Kim and S.J.…”
Section: Figure 10mentioning
confidence: 99%
“…Glibenclamide treatment affects ischemic preconditioning, exposing a possible higher risk of cardiovascular mortality in sulfonylurea-treated type 2 diabetic patients with myocardial infarction (44). In addition, myocardial function during ischemic challenge was found to be altered to a higher degree in glibenclamide-treated compared with insulintreated type 2 diabetic subjects (45).…”
Section: Adverse Effects Of Oral Hypoglycemicmentioning
confidence: 99%